2013
DOI: 10.1590/s1516-35982013000800008
|View full text |Cite
|
Sign up to set email alerts
|

Maternal offspring behaviour in Curraleiro Pé Duro naturalized cattle in Brazil

Abstract: -The objective of the present study consisted of describing dam and calf suckling behaviour of Curraleiro Pé Duro cattle. In this study, 38 mother-offspring pairs and one mother-offspring-orphan trio were observed for 10 hours daily during three consecutive days spaced every four months over a period of one year. After identification, the animals were observed under field conditions where calf posture and the number of suckling episodes (NS), mean suckling duration (MSD), total suckling duration per day (TSD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…A introdução das práticas de vacinação e vermifugação no momento da desmama pode ter contribuído para o aumento de sororreatividade na faixa C (16,1%), pois nessas propriedades a desmama ocorre naturalmente em torno de 9 e 11 meses de idade para fêmeas e machos, respectivamente 23 . A distribuição dos animais sororreagentes ampliou-se a partir dos 36 meses de idade, sugerindo que alguns fatores envolvidos na disseminação do agente não puderam ser determinados e apontando para a necessidade de uma investigação aprofundada sobre a epidemiologia da LB.…”
Section: Resultsunclassified
“…A introdução das práticas de vacinação e vermifugação no momento da desmama pode ter contribuído para o aumento de sororreatividade na faixa C (16,1%), pois nessas propriedades a desmama ocorre naturalmente em torno de 9 e 11 meses de idade para fêmeas e machos, respectivamente 23 . A distribuição dos animais sororreagentes ampliou-se a partir dos 36 meses de idade, sugerindo que alguns fatores envolvidos na disseminação do agente não puderam ser determinados e apontando para a necessidade de uma investigação aprofundada sobre a epidemiologia da LB.…”
Section: Resultsunclassified
“…This breed was reared under diverse farming conditions, with minimum health care and nutrition, resulting in animals resistant to endoparasites and ectoparasites, and low production costs [ 11 ]. In common, these two breeds show rusticity, regional disease resistance, ability to tolerate long periods of dietary restriction and rapid recovery of body weight after periods of feed restriction [ 12 ]. Due to natural selection in adverse conditions, especially nutritional aspects, these animals are generally smaller compared to commercial breeds [ 13 , 14 ] and can take up to four years to be slaughtered in diverse farming systems [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some breeds display more maternal behavior than others, establishing the mother-young bond more strongly. For example, Curraleiro Raza Pé Duro cows frequently abandon their offspring to look for water and food, which could disrupt the development of the mother-calf bond during the sensitive period [120], while Dorset horned ewes and some hybrid mothers (Border Leicester X Merino) show greater maternal capacity, staying with their lambs even during human handling. On the contrary, it has been reported that there is a high frequency of abandonment of the offspring by Merino or Romney sheep [111].…”
Section: Factors Inherent To Animalsmentioning
confidence: 99%